Сharacterization of ARC-PVD ZrN nanostructured coatings by using the fractals theory - Romaniuk, S.P.; Volchuk, V.M.; Taran, A.V.; Nowakowska-Langier, K.; Byrka, O.V. (Problems of Atomic Science and Technology, 2022)
Nanostructured ZrN coatings for hardening of a thin-walled cutting tools operating under cyclic loads conditions have been obtained and investigated. The structure and mechanical properties of nanocoatings have been examined. It was revealed that the ZrN coating improved the properties of thin-walled cutting tools. ZrN surface morphology was theoretically substantiated with the application of the fractals theory. Отримано та досліджено наноструктуровані покриття ZrN для зміцнення тонкостінних ріжучих інструментів, що працюють в умовах циклічних навантажень. Досліджено структуру та механічні властивості нанопокриттів. Виявлено, що покриття ZrN покращує властивості тонкостінних ріжучих інструментів. Морфологія поверхні ZrN теоретично обґрунтована із застосуванням теорії фракталів.